The effect of foreign aid on foreign direct investment iInflows: Evidence from Africa - Michael, Joseph (AUC Knowledge Fountain, 2018)
This thesis examines the impact of foreign aid on foreign direct investment (FDI) in Africa. Since there is no consensus in the literature regarding the effects of foreign aid on FDI in developing countries, the thesis examines the empirical relationship between foreign aid and FDI in Africa covering 41 African countries between 1995 and 2015. The analysis controls for market size, level of development, economic trade openness, political stability, and natural resources dependency. The model is estimated using a dynamic panel of System Generalized Method of Moments (GMM) estimation to address endogeneity problem. The model is applied to panel data compiled from publicly available databases. The results of this analysis show support of initial hypotheses that foreign aid can have positive impact on FDI. In addition, while recent studies tend to consider disaggregating aid sectors for infrastructure, and education among others, this thesis argues that aid function channels more impact on a country’s economy rather than being confined to targeted sectors. The results also indicate a significant positive impact associated with development aid channeled through multilaterals on FDI inflows. Consequently, governments’ policies to increase FDI must account for efficient utilization of foreign aid where as policies need to be developed not in isolation from each other. In addition, development partners should channel more funds through multilateral institutions to maximize the effectiveness of foreign aid.